Implementation of Investment Company Licensing in the KITS (Case Study: Waste Pollution by Domestic Investors) - Amanda Satyawati; Duhita Driyah Suprapti (Universitas Negeri Semarang, 2026)
The paradigm shift in licensing through Law No. 6 of 2023 on Job Creation introduced the Risk-Based Business Licensing System (PBBR), which shifted state control from ex-ante to ex-post. However, the efficiency of this investment faces serious challenges in terms of environmental sustainability, as occurred in the Terboyo Industrial Area in Semarang (KITS) where waste leakage caused mass fish deaths in May 2025. This study aims to analyze the implementation of risk-based licensing for Domestic Investment Companies (PMDN) and evaluate the mechanism for monitoring environmental compliance in the field. The method used is juridical-sociological with a descriptive qualitative approach. Primary data was obtained through interviews with the Semarang City Environmental Department and the Investment and One-Stop Integrated Services Agency of Central Java Province, while secondary data included legislation and related legal literature. The results of the study show that although the OSS-RBA system has improved bureaucratic efficiency and time certainty for business actors, there is a significant gap between das sollen and das sein. Weak coordination and unsynchronized monitoring frequency between technical agencies and area managers create compliance gaps that weaken early detection of pollution. Evidently, the TDS parameter of the waste reached 23,510 mg/L, far exceeding the threshold of 1,000 mg/L. Policy redesign is needed through strengthened periodic monitoring by technical agencies and the enforcement of strict sanctions based on the principle of strict liability to ensure bureaucratic reforms maintain the principles of sustainable development.